Tuberculosis Terpene Targets. Issue 4 (23rd April 2015) - Oldfield, Eric
Abstract : In this issue, Young, Moody, and colleagues report the discovery of an isomer of the Mycobacterium tuberculosis (Mtb) virulence factor 1-tuberculosinyl adenosine, N 6 -tuberculosinyl adenosine, in mice infected with tuberculosis. These Mtb-derived terpene compounds may serve as sensitive and specific biomarkers of infection.